Our Unique Experience with Low-Dose Alemtuzumab as an Induction Agent for Renal Transplantation: A Case Series - Cherin Josi; Arjun Parthasarathy; Divya Sundar; Milly Matthew; Premkumar Rajendran; Georgi Abraham (Indian Journal of Transplantation)
The use of an induction agent in renal transplant is based on the center or physician’s protocol. Alemtuzumab was used as an induction agent in 1998 for the first time and has been used since then as an induction agent off-label. There has been no consensus on the dosage of alemtuzumab. We describe our experience of using low-dose alemtuzumab in 13 patients who have undergone live-related kidney transplantation. Twelve patients received Alemtuzumab 15 mg as a single dose intravenous (IV) on day 0 along with methylprednisolone. One patient received 10 mg of alemtuzumab. Tacrolimus, mycophenolate mofetil, and steroids were the maintenance immunosuppressive agents. Postoperatively, white blood cell and differential count and renal function were monitored daily. We transplanted 13 patients, 2 females and 11 males, including one pediatric patient. The mean age of the patients was 33 (±12) years. All the patients underwent live donor kidney transplants. One patient had regrafting. All the patients had their CDC and flow crossmatch done and were negative. They had end-to-side anastomosis with the external iliac artery, and the cold ischemia time was around 22 min. The mean absolute lymphocyte count before the transplant was 1520 (±627)/mm3, and posttransplant, it was 30 (±16)/mm3; the mean creatinine was 1.0 (±0.2) on discharge. None of the patients had any episode of rejection. There were five episodes of urinary tract infection and one episode of wound infection among the patients. Alemtuzumab, given in a dose of 15 mg IV (50% reduction), is a useful induction adjuvant and can be a cost-effective strategy for induction in renal transplant recipients to prevent acute rejection.